SISTEM PENDUKUNG KEPUTUSAN UNTUK PRIORITAS PENGADAAN OBAT DENGAN METODE PARETO ABC - Muhammad Furqon Huwaidy; Taufik Ridwan; Bagja Nugraha (Jurnal Komputer dan Teknologi, 2026)
Efficient drug procurement management is an important challenge for pharmacies, especially in avoiding the risks of overstocking and stockouts that can affect service quality. This study aims to develop a web-based Decision Support System (DSS) that helps determine drug procurement priorities at Qita Sehat Pharmacy using the Pareto ABC method. This method categorizes drugs into A, B, and C based on usage and investment values, facilitating more strategic and data-driven decision-making. The system was developed using the Waterfall model of the Software Development Life Cycle (SDLC) approach, through the stages of requirements analysis, design, coding, and testing. The system was designed using PHP, HTML, Bootstrap, and MySQL as the database. Key features include drug data management, Pareto calculations, and downloadable analysis reports. Testing was conducted through alpha testing using the black box method to ensure system functionality, as well as beta testing with saturated sampling techniques on internal pharmacy users. The test results showed that the system ran stably and according to specifications. The user acceptance index of 79% indicates that the system has met the aspects of functionality, reliability, ease of use, efficiency, and portability.